2018
DOI: 10.1039/c8ra02368a
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide based active catalyst for hydroxylammonium nitrate (HAN) fueled monopropellant thrusters

Abstract: The developed doped ceria catalyst is a new type of high temperature and poisoning resistant catalyst for decomposition of hydroxylammonium nitrate monopropellant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…The procedure to prepare catalysts used in the present study is reported in our earlier work [21]. Iridium catalyst (Ir/γ‐Al 2 O 3 ) was prepared by wet impregnation of gamma alumina support (make Alfa Aesar; surface area (200 m 2 /g) catalyst pellets) using hexachloroiridic acid as active metal precursor.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The procedure to prepare catalysts used in the present study is reported in our earlier work [21]. Iridium catalyst (Ir/γ‐Al 2 O 3 ) was prepared by wet impregnation of gamma alumina support (make Alfa Aesar; surface area (200 m 2 /g) catalyst pellets) using hexachloroiridic acid as active metal precursor.…”
Section: Methodsmentioning
confidence: 99%
“…Iridium catalyst (Ir/γ‐Al 2 O 3 ) was prepared by wet impregnation of gamma alumina support (make Alfa Aesar; surface area (200 m 2 /g) catalyst pellets) using hexachloroiridic acid as active metal precursor. Cerium oxide catalyst was prepared from ceric ammonium nitrate and cobaltous nitrate by coprecipitation method followed by sintering of prepared pellets as reported earlier [21].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, ADN-based liquid monopropellants consisting of an ADN aqueous solution, methanol, and ammonia were commercialized [5]. An HAN-based liquid monopropellant was also used in aqueous solutions [6,7]. ADN and HAN are highly energetic compounds, and the decomposition of ADN-and HAN-based 2 of 15 liquid monopropellants does not generate halogen compounds.…”
Section: Introductionmentioning
confidence: 99%